Regional variability and driving forces behind forest fires in Portugal an overview of the last three decades (1980–2009) - Nunes, Adélia de Jesus Nobre (2012)
The purpose of this paper was to analyze the evolution and regional distribution of both forest fire ignitions and burnt areas in mainland Portugal and to identify the relationship between biophysical and human variables and the incidence of forest fires at the district level over the last 3 decades (1980–2009). A positive trend can be observed in the number of fires and in the areas burnt by forest fires since 1980. An interesting regional distribution of forest fire ignitions and burned areas was detected, highlighting some districts especially vulnerable to the outbreak of fires and others particularly susceptible to the spread of fire. A stepwise multiple regression methodology was applied to determine the relative importance of each variable in explaining the regional distribution of ignitions and burned area fractions and to address hypotheses regarding human and biophysical influences on the drivers of forest fires. Population density was the primary determining variable in the outbreak of fires at the district level (this factor alone explained 65% of the inter-district variation in the density of fire ignitions), whereas burn areas were influenced by the synergistic effects of topography, changes in land use, and vegetation. The topographic roughness index emerged as the most important variable causing the regional variations observed in the percentage of the district area burnt over the last 30 years, explaining 70% of the observed variance. Variables associated with changes in land use and cover during the second half of the last century explained an additional 17% of the variance. Multiple regression analysis also suggested a positive relationship between the total area burnt and the total uncultivated area, explaining 57% of the variance at the district level. In general, the greatest pressures from fire occur in the districts north of the Tejo River, which are more mountainous, have lower annual temperatures and more rainfall, and produce the most biomass under pressure from agriculture and grazing. In these districts, the decline of traditional agriculture has resulted in important transformations to the landscape characterized by the spread of natural vegetation.